Traits of insect herbivores and target weeds associated with greater biological weed control establishment and impact - Sujan Panta; Mark Schwarzländer; Philip S. R. Weyl; Hariet L. Hinz; Rachel L. Winston; Sanford D. Eigenbrode; Bradley L. Harmon; Sven Bacher; Quentin Paynter (BioControl, 2024)
Improving success rates of classical weed biocontrol programs is an ongoing effort that requires a variety of different approaches. Previous assessments indicated biocontrol agent taxonomy and feeding characteristics and weed life history traits are associated with better control outcomes. We examined weed biocontrol releases for correlations between biocontrol agent and target weed traits associated with different levels of reported establishment and control. Data collated in the 5th edition of ‘Biological Control of Weeds: A World Catalogue of Agents and Their Target Weeds’ were used as the basis for this global analysis. Published literature was used to augment the catalog with data for eight biocontrol agent traits and four target weed traits. Biocontrol agent establishment and impact data were analyzed against these traits using generalized linear mixed models and categorical models, respectively. Analyses for biocontrol agent establishment reveal the following agent traits were correlated with a greater probability of establishment: being an internal feeder, feeding on above-ground plant tissues, multivoltine agents and agents that feed during both their adult and immature life stages. Insect taxon did not affect establishment except for the order Lepidoptera, which had the lowest establishment probability. For weed traits, those occurring in aquatic or riparian habitats were associated with a higher probability of biocontrol agent establishment. Regarding agent impact, using the definition categories in the catalog, agents feeding externally and on vegetative plant tissues, multivoltine agents and those with both adult and immature plant-feeding life stages were strongly correlated with greater impact. Perennials, reproducing only vegetatively and invading aquatic or riparian habitats were associated with greater biocontrol impact. Our findings could facilitate both the prioritization of invasive plants targeted for biocontrol and the selection of suitable biocontrol agent candidates, which should further improve biocontrol project outcomes.